Konkurencyjność polskich produktów rolno-spożywczych na tle wymiany zagranicznej z głównymi partnerami handlowymi - Puchalska, Katarzyna; Kalita, Waldemar (International Competitiveness of Polish Farm-Food Products Trade Against the Background of Exchange of Goods with Main Co-Operative Partners, 2006)
The competitiveness is one of the most important factors determining the volume of trade соn-ducted by a given commodity group. In the researched period we dominated our main co-operative partners i.e. Germany, France, Great Britain and Italy, and we had the competitive advantage in trade food, over them, which remains steady. The possibilities of improvement in competitive advantage still exist but they are not easy to be put into practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 267-272